FONEM SEGMENTAL BAHASA KANUM SOTA - Yohanis Sanjoko (Balai Bahasa Provinsi Papua, 2019)
This research discusses about segmental fonems of Kanum language in Indonesian-Papua New Guinea boarder area. Kanum language is a local language in Merauke, Papua that spoken by Sota people. This research uses descriptive method by three steps, consist of the data preparing, data analizing, and presentation the result of analizing data. Analizing data do after collection data was classified. It was done by distributional method. The result of this research shows Kanum Sota language have 19 consonant, that are /p/, /b/, /t/, /d/, /c/, /j/, /k/, /g/, /m/, /n/, /G/, /ñ/, /l/, /f/, /s/, /h/, /r/, /w/, /y/, dan 6 buah fonem vokal, yaitu /a/, /i/, /u/, /e/, /|/, dan /O/.